The Relationship among Professional Baseball Teams' Integrated Marketing Communication (IMC) Attributes, Fans' Perceived Value and Voluntary Behavior related to a Parent Company - Jooyoung Kim; Susan Kim (Korea Institute of Sport Science, 2023)
PURPOSE The purpose of this study was to investigate the relationship between the integrated marketing communication (IMC) attribute of professional baseball teams, their fans' perceived value, and voluntary behavior related to the parent company. METHODS In this study, the target population consisted of spectators watching a professional baseball game. A survey was conducted on 360 fans watching the KIA tigers' and kt wiz' home game using the convenience sampling method. Finally, a total of 261 were used for data analysis, and frequency, confirmatory factor, reliability, correlation, structural equation model analyses using SPSS 20.0 and AMOS 20.0. RESULTS Main findings are as follows: First, interactivity of professional baseball teams' IMC had positive effects on the emotional value. Second, interactivity and reminders from the parent companies of professional baseball teams' IMC had positive effects on social value. Third, stakeholder connectivity and reminders from parent company of professional baseball teams' IMC had positive effects on altruistic value. Fourth, with regard to the social aspect, the fans' perceived value had positive effects on loyalty, customer participation and customer cooperation of voluntary behavior related to parent company. Lastly, with regard to the altruistic aspect, the fans' perceived value had positive effects on customer cooperation of voluntary behavior related to the parent company. CONCLUSIONS Therefore, professional baseball teams should identify the IMC elements that fans perceive as important and establish effective marketing communication strategies to enhance the perceived value of their brand among their fans, ultimately increasing their voluntary engagement with the parent company.